1988
DOI: 10.1212/wnl.38.4.634
|View full text |Cite
|
Sign up to set email alerts
|

Ictal speech, postictal language dysfunction, and seizure lateralization

Abstract: In 84 patients with complex partial seizures evaluated by EEG and video telemetry, who went on to have seizure surgery, complex intraictal vocalizations and postictal language dysfunction were found to have strong lateralizing significance. Thirteen patients had ictal speech, and 12 of these had right-sided seizure foci. Twenty-eight had intact postictal language, and 21 of these had right-sided foci. Of the 32 with impaired postictal language, 21 had left-sided foci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
32
0
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 0 publications
5
32
0
1
Order By: Relevance
“…2 The appearance and disappearance of aphasia, with corresponding EEG findings, confirm ictal but not post-ictal manifestations. 7 On literature review, NKH-related ASE seems to have its initial presentation as mixed aphasia, 6 the same as in our case. This kind of aphasia is similar to that of patients with left middle cerebral artery infarction, which is the leading cause of isolated aphasia, making it more difficult to establish accurate diagnosis of NKH-related ASE.…”
Section: Discussionsupporting
confidence: 69%
“…2 The appearance and disappearance of aphasia, with corresponding EEG findings, confirm ictal but not post-ictal manifestations. 7 On literature review, NKH-related ASE seems to have its initial presentation as mixed aphasia, 6 the same as in our case. This kind of aphasia is similar to that of patients with left middle cerebral artery infarction, which is the leading cause of isolated aphasia, making it more difficult to establish accurate diagnosis of NKH-related ASE.…”
Section: Discussionsupporting
confidence: 69%
“…Postictal dysphasia has repeatedly been demonstrated to be consistent with a seizure onset in the dominant hemisphere [22, [34][35][36][37]. Our results confirmed these reports.…”
Section: Discussionsupporting
confidence: 90%
“…Useful ictal lateralizing signs in patients with temporal lobe CPS include contralateral dystonic posturing (13-16), ipsilateral manual aUtOmatisms (14) [possibly only in combination with contralateral dystonic posturing (1 5 ) 1 7 nonforced ipsilateral head deviation ( l 7)7 forced contralateral head deviation before secondarily generalized activity (13)(14)(15)17,18), contralateral immobile limb (13, 16,19), ictal speech (14,18,20,21) (nondominant hemisphere), and ictal vomiting (1 1,22) (right hemisphere). However, many patients with temporal lobe epilepsy (TLE) manifest none of these features (14,23).…”
mentioning
confidence: 99%
“…However, it is rare in TLE (23). Other postictal signs with potentially useful lateralizing information include flattened affect and prolonged disorientation to place (26) (right hemisphere), unilateral extensor plantar response (27), and postictal aphasia (14,18,20,21,23,28,30) (dominant hemisphere). Some investigators have reported that postictal aphasia appears to reflect the site of origin of the seizure independent of the subsequent spread (26,28).…”
mentioning
confidence: 99%